Disrupsi dan Eksistensi Pustakawan di Jaman Teknologi Informasi - Dwi Astutiningsih (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
Librarians, those who work in libraries or similar institutions and have formallibrary education (at least D2 perpustakaan.Disrupsi / dis * rup · si / n according to the Indonesian Big Dictionary means : the thing is revoked from the root. Disruption (disrupsi) situations in which industrial world movement or work competition is no longer linear, changes are very fast, fundamentally by ruffling old patterns of order to create new order Librarians are one of the professions that will be disrupted by changes in information technology.In the era of information technology, the role of librarians is needed in information literacy. As we know that information literacy is a person’s ability to recognize when information is needed as well as a set of skills a person has in finding, discovering, analyzing, evaluating, and communicatinginformation that functions in meeting the information needs that will solve various problems. So librarians should be able to provide skills to a person to be able to access and obtain information about their health, the environment, their education, their work, etc., guide the pemuska in making the right decisions about their lives, and be more responsible for the health and education of the user, so that pemustaka able to take decisions, become human learners in the information age, and able to create new knowledge.